Beating-Heart Coronary Artery Bypass grafting (BH-CABG) in patients with End-Stage Renal Disease (ESRD): comparison of the Society of Thoracic Surgeons (STS) predicted risk with actual outcomes - Louis Samuels; Anastasia Arce; Samiat Agunbiade; Suzanne Raws; Afshin Parsikia (Journal of Cardiothoracic Surgery)
Abstract Background End-Stage Renal Disease (ESRD) is an independent risk factor in outcomes for traditional coronary artery bypass grafting (TRAD-CAB) utilizing aortic cross-clamping and cardioplegic arrest. In order to determine if Beating-Heart CABG (BH-CABG) techniques offer benefit in patients with ESRD, an analysis of the Society of Thoracic Surgeons (STS) predicted risk versus the actual outcomes was performed. Methods Between March 2017 - October 2023, all ESRD patients underwent BH-CABG by a single surgeon at a single institution. Patients were kept normothermic, ventilation was maintained, and intra-coronary shunts with flow-probe graft assessment were utilized during the procedure. The STS predicted risk calculator was used to compare outcomes with actual results. Results There were 55 patients– 37 men and 18 women with a mean age of 61.5 years (41–77 years). Co-medical conditions consisted of the following: HTN (100%), DM (85%), Pulmonary HTN (49%), PVD (45%), CVD with CVA (18%), and COPD (9%). Fifty-one patients underwent Pump-Assisted Direct Coronary Artery Bypass Grafting (PADCAB) and four underwent Off-Pump CABG (OP-CAB). There were 16 Elective, 35 Urgent, and 4 Emergent cases. Case presentation included: 24 NSTEMI, 4 STEMI, 6 Unstable Angina, 7 CHF, 1 Cardiac Arrest, and 13 with a positive exercise stress test (EST) for renal transplant screening. The mean EF was 47% (range: 15–75%). The mean number of grafts was 2.4 (1–4) and CPB time was 78 min (34–128 min) for the PAD-CAB group. Nine of the thirteen patients (69%) listed for kidney transplant underwent the transplant, one of whom was a combined liver-kidney. There was 1 hospital mortality (1.8%) compared to a predicted 6.2%. There was 1 stroke (1.8%) compared to a predicted 3.3%. There was 1 prolonged ventilation (1.8%) compared to a predicted 20.2%. There were no return to OR and no sternal wound infections. Prolonged Lengths of Stay occurred in 3 patients (5.5%) compared to a predicted 16.9%. One-year mortality occurred in 8 patients (14.5%). The observed-to-expected outcomes was < 1 in all categories. Conclusions The BH-CABG appears to demonstrate superior outcomes compared to the STS predicted risk for CABG. The Beating-Heart technique may offer advantages by avoidance of aortic cross-clamping and cardioplegia, maintenance of normothermia and ventilation, as well as preservation of coronary blood flow during construction of bypass grafting.